Cylindrically confined assembly of diblock copolymer under oscillatory shear flow - Guo, Y.-Q.; Pan, J.-X.; Zhang, J.-J.; Sun, M.-N.; Wang, B.-F.; Wu, H.-Sh. (Condensed Matter Physics, 2016)
Manipulating the self-assembly nanostructures with combined different control measures is emerging as a
promising route for numerous applications to generate templates and scaffolds for nanostructured materials.
Here, the two different control measures are a cylindrical confinement and an oscillatory shear flow. We study
the phase behavior of diblock copolymer confined in nanopore under oscillatory shear by considering different
D/L₀ (D is the diameter of the cylindrical nanopore, L₀ is the domain spacing) and different shears via Cell
Dynamics Simulation. Under different D/L₀ , in the system occurs different morphology evolution and phase
transition with the changing of amplitude and frequency. Meanwhile, it forms a series of novel morphologies.
For each D/L₀ , we construct a phase diagram of different forms and analyze the reason why the phase transition occurs. We find that although the morphologies are different under different D/L₀ , the reason of the
phase transition with the changing of amplitude and frequency is roughly the same, all caused by the interplay
of the field effect and confinement effect. These results can guide an experimentalist to an easy method of
creating the ordered, defect-free nanostructured materials using a combination of the cylindrical confinement
and oscillatory shear flow. Керування самоскупченими наноструктурами з допомогою поєднання рiзних заходiв керування виявляється багатообiцяючим шляхом для чисельних застосувань для генерування шаблонiв для наноструктурованих матерiалiв. У цiй статтi двома рiзними заходами керування є цилiндричне обмеження та осциляцiйний зсувний потiк. Дослiджується фазова поведiнка дiблочного кополiмера, обмеженого нанопорою
пiд дiєю осциляцiйного зсуву з врахуванням рiзних D/L₀ (D — це дiаметр цилiндричної пори, L₀ — це
розмiр домена) та рiзних зсувiв з допомогою симуляцiй комiркової динамiки. При рiзних D/L₀ , в системi вiдбувається еволюцiя рiзної морфологiї i фазовий перехiд зi змiною амплiтуди i частоти. Тим часом,
утворюється ряд нових морфологiй. Для кожного D/L₀ , ми будуємо фазову дiаграму рiзних форм та аналiзуємо причини здiйснення фазового переходу. Встановлено, що, хоча морфологiї вiдрiзняються при
рiзних D/L₀ , причина фазового переходу при змiнi амплiтуди i частоти є приблизно однаковою, а саме вона полягає в поєднаннi польового ефекту i ефекту просторового обмеження. Цi результати можуть
дати експериментаторам простий метод створення впорядкованих, бездефектних наноструктурованих
матерiалiв за рахунок поєднання цилiндричного обмеження та осциляцiйного зсувного потоку.